2000
DOI: 10.1103/physrevlett.84.3097
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Attainment of High Electron and Ion Temperatures in Discharges with Internal Transport Barriers in ASDEX Upgrade

Abstract: Internal transport barriers have been demonstrated to exist also under conditions with T(e) approximately T(i) approximately 10 keV and predominant electron heating of the tokamak core region. Central electron cyclotron heating was added to neutral beam injection-heated ASDEX Upgrade discharges with a preexisting internal transport barrier, established through programmed current ramping leading to shear reversal. Compared to a reference internal transport barrier discharge without electron cyclotron resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…(d) The constraint (7) depends on τ e = T e /T i via the coefficient D in such a manner that the range of validity of the assumption w l,m < ∆ l,m , and therefore of the expression (6a) of the growth rate, extends to higher poloidal mode numbers if T e /T i increases. This favourable trend (we note that there is a rapid increase of the growth rate when the condition w l,m < ∆ l,m is no longer fulfilled) explains why transport barriers, first observed in plasmas with predominantly ion heating and characterized by τ e < 1, are maintained when τ e ∼ 1 [6]. This result is important for reactors with predominant heating by thermonuclear α particles.…”
Section: Initiation Of Ion Itbs In Ncs Dischargesmentioning
confidence: 67%
See 1 more Smart Citation
“…(d) The constraint (7) depends on τ e = T e /T i via the coefficient D in such a manner that the range of validity of the assumption w l,m < ∆ l,m , and therefore of the expression (6a) of the growth rate, extends to higher poloidal mode numbers if T e /T i increases. This favourable trend (we note that there is a rapid increase of the growth rate when the condition w l,m < ∆ l,m is no longer fulfilled) explains why transport barriers, first observed in plasmas with predominantly ion heating and characterized by τ e < 1, are maintained when τ e ∼ 1 [6]. This result is important for reactors with predominant heating by thermonuclear α particles.…”
Section: Initiation Of Ion Itbs In Ncs Dischargesmentioning
confidence: 67%
“…Analysis of negative central shear (NCS) tokamak discharges has shown that an ion internal transport barrier (ITB) may develop near the position where the safety factor q reaches its minimum [1][2][3][4][5][6]. There is also evidence that, in addition to the NCS q profile, E × B flow shear in the core plays an important role in stabilizing turbulence [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1]) and ASDEX Upgrade (Ref. [2]) tokamaks. Theoretically, there has been an increasing number of studies on the equilibrium and stability properties of flowing plasmas (see, for example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In these experiments, the radial profiles of rotational transform ͑safety factor͒ are measured or calculated and the role of magnetic shear in the formation of the electron internal transport barrier is discussed and the role of radial electric field E r shear on the electron and ion transport barrier has been studied in tokamak plasma. 7,8 In stellarator plasmas, both the electron and ion ripple losses are sensitive to the radial electric field and electron and ion radial fluxes are functions of the radial electric field in the plasma.…”
Section: Introductionmentioning
confidence: 99%